2014
DOI: 10.1155/2014/967585
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Whole Genome MicroRNA Expression Profiling in Childhood Acute Lymphoblastic Leukemia

Abstract: Dysregulation of microRNA (miRNA) expression contributes to the pathogenesis of several clinical conditions. The aim of this study is to evaluate the associations between miRNAs and childhood acute lymphoblastic leukemia (ALL) to discover their role in the course of the disease. Forty-three children with ALL and 14 age-matched healthy controls were included in the study. MicroRNA microarray expression profiling was used for peripheral blood and bone marrow samples. Aberrant miRNA expressions associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 36 publications
3
53
0
2
Order By: Relevance
“…If miR-146a is overexpressed in hematopoietic stem cells and bone marrow transplantation is conducted, instantaneous marrow expansion will occur, erythropoiesis will be reduced and lymphocytopoiesis will be suppressed (8). Increased miR-146a expression is deleterious for marrow reconstruction in mice and reduces the survival rate of hematopoietic stem cells (9).…”
Section: Discussionmentioning
confidence: 99%
“…If miR-146a is overexpressed in hematopoietic stem cells and bone marrow transplantation is conducted, instantaneous marrow expansion will occur, erythropoiesis will be reduced and lymphocytopoiesis will be suppressed (8). Increased miR-146a expression is deleterious for marrow reconstruction in mice and reduces the survival rate of hematopoietic stem cells (9).…”
Section: Discussionmentioning
confidence: 99%
“…Later on, several studies reported dysregulated miRNA expression in pediatric ALL samples compared to normal cells. For example, a number of publications described increased expression of miR-21, miR-34, miR-128, miR-142, miR-146a, miR-181b, miR-195, and miR-708 [ 19 , 20 , 21 , 22 , 23 ], and decreased levels of miR-18, miR-181a, miR-99a, miR-100, miR-145, let-7, and miR-196b in ALL cells [ 19 , 21 , 24 , 25 ].…”
Section: Leukemiasmentioning
confidence: 99%
“…The expression of some miRNAs can be used to monitor disease progression, such as with miR-128, miR-146a, miR-155, miR-181a, and miR-195 [ 21 ]. In addition, miR-210 has been proposed as a good prognostic factor and a useful predictor of drug sensitivity [ 53 ].…”
Section: Leukemiasmentioning
confidence: 99%
“… 66 Other groups also have performed analogous studies to discover miRNAs expression signatures of ALL. 67 70 …”
Section: The Function Of Mirnas In Allmentioning
confidence: 99%